2014
DOI: 10.1093/mutage/geu076
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in lncRNA HOTAIR are associated with risk of colorectal cancer

Abstract: Long non-coding RNA HOX transcript antisenseRNA (HOTAIR) has been widely identified to participate in tumour pathogenesis, acting as a promoter in colorectal cancer carcinogenesis. However, the association between genetic variants in HOTAIR and cancer risk has not yet been reported. In the present study, we performed a two-stage case-control study to investigate the association between HOTAIR tagSNPs and the risk of colorectal cancer. We found that individuals with rs7958904 CC genotype had a significantly dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
105
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 26 publications
1
105
1
Order By: Relevance
“…Moreover, individuals with C alleles for rs7958904 presented a low risk of acquiring EOC [14]. In a parallel study, Xue et al [45]. reported that the HOTAIR SNP rs7958904 was associated with a low risk of colorectal cancer.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, individuals with C alleles for rs7958904 presented a low risk of acquiring EOC [14]. In a parallel study, Xue et al [45]. reported that the HOTAIR SNP rs7958904 was associated with a low risk of colorectal cancer.…”
Section: Introductionmentioning
confidence: 98%
“…Multiple previous studies have reported that lncRNAs are involved in cancer pathogenesis and may provide novel insight into the biology of this disease (5,6), where they may act as oncogenes or tumor suppressors. A number of previous studies have reported that HOTAIR may possess pro-oncogenic functions and that it is involved in multiple cancers (8)(9)(10)(11)(12). Similarly, a number of studies have demonstrated that HOTTIP may serve as a critical regulator in certain cancers.…”
Section: Discussionmentioning
confidence: 99%
“…HOTAIR is a lncRNA of 2,158 nucleotides in length, which is expressed in the HOXC locus of chromosome 12 (7). It has been reported to be a pro-oncogenic factor and a negative prognostic factor in several types of cancer, including breast, pancreatic, gastric, colorectal and bladder cancer (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…The assay was performed as described previously [21]. Briefly, approximately 5 × 10 3 cells transfected with HOTAIR-CC expression construct or HOTAIR-TT expression construct were plated in 96-well plates.…”
Section: Methodsmentioning
confidence: 99%